Prevalence and molecular characterization of human bocavirus in children with acute gastroenteritis in Beijing, China, during 2014–2023 - Zeng Li; Kexiang Zhang; Ri De; Zhenzhi Han; Yanpeng Xu; Liying Liu; Liping Jia; Huijin Dong; Hui Huang; Li Deng; Linqing Zhao (Microbiology Spectrum)
ABSTRACT Human bocavirus (HBoVs) is an emerging virus globally, and its prevalence, diversity, and evolution in children with acute gastroenteritis require further study. Fecal specimens collected from outpatients with acute gastroenteritis in Beijing, China, from April 2014 to December 2023, were tested for HBoVs by PCR targeting the NS1 gene. Genotyping was based on the NP1/VP1 boundary region, and nearly full-length HBoV2 sequences were analyzed phylogenetically. A total of 79 HBoVs-positive specimens (2.5%, 79/3,116, 95% CI: 2.0%–3.1%) were detected, with HBoV2 (65.8%, 52/79, 95% CI: 55.4%–76.3%) as the dominant genotype, followed by HBoV1 (25.3%, 20/79, 95% CI: 15.7%–34.9%) and HBoV3 (8.9%, 7/79, 95% CI: 2.6%–15.1%). HBoVs were distributed throughout the year, with higher positive rates observed from August to December 2018–2021. They predominantly infected children younger than 5 years, especially those aged 6–24 months (3.3%, 52/1,591, 95% CI: 2.4%–4.1%). HBoV2C was the prevalent sub-genotype in Beijing. Novel recombination events were detected between HBoV2 sub-genotypes, with breakpoints in the NS1 and VP3 gene regions. Evolutionary analysis estimated the time to the most recent common ancestor (tMRCA) for HBoV2 dating back to 1845, with a mean nucleotide substitution rate of 1.4 × 10−4 substitutions/site/year, and that HBoV2A evolved faster than HBoV2C. The evolutionary rates decreased in the following order: NP1, VP3, VP1, and NS1. A purifying selection was observed on HBoV2 genes, with one positively selected site in the NS1 gene. In conclusion, HBoV2 was the dominant genotype in children with acute gastroenteritis in Beijing, China, with higher susceptibility in those under 2 years old. Novel recombination events between HBoV2 sub-genotypes occurred frequently.IMPORTANCEAcute gastroenteritis remains a leading cause of morbidity and mortality in children, with viral infections being the primary causative agents. In this study, we investigated the prevalence of human bocavirus (HBoVs) in children with acute gastroenteritis in Beijing from 2014 to 2023, identifying HBoV2C as the predominant sub-genotype. Additionally, this study reported the first estimate of the evolutionary rate for global HBoV2 (1.4 × 10−4 substitutions/site/year) and identified novel intra-genotype recombination events in HBoV2. The results not only filled a gap in the evolutionary studies of global HBoV2 but also offered valuable data for the development of effective surveillance and prevention strategies for controlling acute gastroenteritis in children.